Advances, challenges, and perspectives of biogas cleaning, upgrading, and utilisation - Golmakani, Ayub; Nabavi, Seyed Ali; Wadi, Basil; Manovic, Vasilije (Elsevier, 2022)
Biogas as a renewable energy resource can be broadly recognised as a carbon–neutral fuel which reduces anthropogenic greenhouse gas emissions, mitigates global warming, and diversifies energy supply. However, the biogas share in the global renewable energy supply chain and technology deployment and maturity are not commensurate with the potential. The first half of this study critically reviews state of the art developments in biogas cleaning and upgrading technologies by considering their present status, current challenges, and barriers associated with their future development. The second part of this paper aims to address critical gaps in converting biogas to biomethane, proposing required pre-treatment steps for different technologies. The third part focuses on current policies concerning the strict regulations implemented for flaring consent applications. In this section, biogas upgrading technologies were compared by estimating the global warming potential (GWP) resulting from waste gases (WG). It was observed that due to high methane losses, WGs from membrane technologies have the highest GWP, but with flaring have the lowest GWP. In the last part of this review, the recent applications of biogas in cogeneration (CHP), tri-generation (CCHP), quad-generation systems, heat, and vehicles are discussed. The use of biogas by different technologies, and their resulting efficiencies were analysed in CHP applications, including microturbines, micro humid air turbine (mHAT), solid oxide fuel cells (SOFC) and hybrid systems of SOFC-microturbines.
Keywords: Biogas cleaning; Biogas upgrading; Biogas utilisation; Biomethane; Global warming potential; Methane emissions